The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.3758/bf03194875
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing a plane-misoriented view of a familiar object is not influenced by the ease of specifying the main axis of elongation of that object

Abstract: Participants saw three versions of pictures of familiar objects: the original unaltered (axis-normal) pictures, axis-extended pictures in which the main axes of the axis-normal pictures were elongated, and axis-switched pictures in which objects that were originally horizontally elongated were depicted as vertically elongated and vice versa. Relative to axis-normal pictures, axis extension aided decisions about whether the picture of the object was wide or tall, and axis switching hindered these decisions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…The finding that performance was largely independent of the objects' main axes is consistent with studies suggesting that the axis of elongation is not the main cue for alignment (Large et al, 2003; Lawson, 2004). However, the results do not exclude the possibility that the main axis is one of several cues for object orientation.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…The finding that performance was largely independent of the objects' main axes is consistent with studies suggesting that the axis of elongation is not the main cue for alignment (Large et al, 2003; Lawson, 2004). However, the results do not exclude the possibility that the main axis is one of several cues for object orientation.…”
Section: Methodssupporting
confidence: 87%
“…For example, is there still a congruency effect when an object with a vertical axis of elongation is followed by an object with a horizontal axis (e.g., a saltshaker followed by a car)? Recent studies showed that the main axis of elongation has only little or no influence on naming performance (Large, McMullen, & Hamm, 2003; Lawson, 2004). However, this does not necessarily mean that congruency effects are independent of the axis of elongation.…”
mentioning
confidence: 99%
“…This is consistent with data from some other studies (e.g., Large et al, 2003;Lawson, 2004;Wilson & Farah, 2003), and places some doubt about the importance of shape axes per se in misoriented object recognition (e.g., Humphreys & Quinlan, 1988;Humphreys & Riddoch, 1984;Quinlan & Humphrey~, 1993). However, further analyses of the current data also showed that an axis of symmetry can be sufficient to attenuate effects of stimulus misorientation: Symmetrical apolar objects showed more shallow regression slopes than asymmetrical objects, consistent with faster spatial normalization.…”
Section: Discussionsupporting
confidence: 83%
“…First, the results showed an interaction between the effects of stimulus orientation on recognition and the presence or absence of object polar features: Larger orientation effects were found for the apolar than for the polar object set. Second, a contrast in orientation effects between the apolar symmetrical objects used in Experiment 2, and the polar asymmetrical objects used in Experiment 1, suggested that the presence of a salient internal shape axis contributes to the attenuation of orientation effects, contrary to some recent data (Lawson, 2004).…”
Section: Discussionmentioning
confidence: 74%